The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/advs.202205580
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐Cell P450 Biocatalysis Using Engineered Escherichia coli with Fine‐Tuned Heme Biosynthesis

Abstract: By exploiting versatile P450 enzymes, whole-cell biocatalysis can be performed to synthesize valuable compounds in Escherichia coli. However, the insufficient supply of heme limits the whole-cell P450 biocatalytic activity. Here a strategy for improving intracellular heme biosynthesis to enhance the catalytic efficiencies of P450s is reported. After comparing the effects of improving heme transport and biosynthesis on P450 activities, intracellular heme biosynthesis is optimized through the integrated expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 73 publications
(110 reference statements)
0
15
0
Order By: Relevance
“…Since the CYP105 family is a three-component P450 enzyme, the most widely studied redox partners CamA (putidaredoxin reductase) and CamB (putidaredoxin) were employed in the whole-cell biocatalysis to transfer electrons from NAD(P)H to the heme-iron reactive center for O 2 activation. Thus, the genes encoding CamA and CamB were co-expressed with these five P450s genes using a pRSFDuet-1 plasmid in the C41(DE3) strain ( Hu et al, 2022a ), respectively, resulting in HFLA-1 to HFLA-5 strains. Subsequently, the hydroxylation of flavonoids by whole-cell as biocatalysts was compared using naringenin as a model substrate ( Figures 2A, B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the CYP105 family is a three-component P450 enzyme, the most widely studied redox partners CamA (putidaredoxin reductase) and CamB (putidaredoxin) were employed in the whole-cell biocatalysis to transfer electrons from NAD(P)H to the heme-iron reactive center for O 2 activation. Thus, the genes encoding CamA and CamB were co-expressed with these five P450s genes using a pRSFDuet-1 plasmid in the C41(DE3) strain ( Hu et al, 2022a ), respectively, resulting in HFLA-1 to HFLA-5 strains. Subsequently, the hydroxylation of flavonoids by whole-cell as biocatalysts was compared using naringenin as a model substrate ( Figures 2A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…P450s are thought to be reliable, effective, and ecofriendly biocatalysts for the synthesis of valuable compounds in recombinant hosts. In addition, compared to the utilization of purified or extracted P450s, whole-cell biotransformation has shown a clear advantage by providing the necessary precursors, the expensive cofactors NAD(P)H, and suitable environments for catalytic reactions ( Hu et al, 2022a ). Moreover, to exploit the versatile P450s for industrial applications, Escherichia coli is a widely applied and efficient system for whole-cell biotransformation ( Park et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…53 Hu et al effectively increased the heme content in E. coli by expressing the heme synthesis gene in appropriate proportions and assembling rate-limiting enzymes using DNA scaffolds. 101 Organic integration of various strategies may further enhance the production of porphyrins synthesized by microorganisms.…”
Section: Metabolic Pathways Of Natural Porphyrin Pigmentsmentioning
confidence: 99%
“…It has been reported that increased ALA concentration leads to decreased P450 content, due to the toxic effect of heme on cells. [28] Furthermore, the heme group contains iron in its center, and thus iron supplementation also affects the efficient production of heme and correctly folded P450 protein. Therefore, different concentrations of FeCl 3 were added to the expression media.…”
Section: Enhanced Expression Of the P450 Azc1mentioning
confidence: 99%